1995
DOI: 10.1128/jb.177.10.2912-2913.1995
|View full text |Cite
|
Sign up to set email alerts
|

Site of phosphorylation of SpoIIAA, the anti-anti-sigma factor for sporulation-specific sigma F of Bacillus subtilis

Abstract: F is regulated by an anti-sigma factor, SpoIIAB, and an anti-anti-sigma factor, SpoIIAA. SpoIIAB also functions as a phosphokinase which transfers phosphate from ATP to SpoIIAA; this phosphorylation is thought to be involved in the regulatory mechanism. By using [␥-32 P]ATP to phosphorylate SpoIIAA, cleaving the protein proteolytically, and analyzing the one resulting radiolabelled peptide by the Edman degradation procedure, we show that the site of phosphorylation in SpoIIAA is Ser-58.Early in the sporulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 10 publications
(6 reference statements)
2
67
0
1
Order By: Relevance
“…From these results, we conclude that: (i) RsbR is a positive regulator which probably belongs to the upstream, environmental-sensing module; (ii) RsbR augments response to salt and heat stress but is not absolutely required for sensing or transmitting these signals; and (iii) RsbR is unique among the known rsb gene products in that it is differentially involved in transmitting some but not all environmental stress signals. Significantly, genetic and biochemical analysis has established that the phosphorylation state of the RsbS, RsbV, and SpoIIAA antagonist proteins is important for their function, and that a conserved serine residue is the probable site of the phosphorylation event (Alper et al, 1994;Diederich et al, 1994;Dufour and Haldenwang, 1994;Najafi et al, 1995;Duncan et al, 1996;Kang et al, 1996;Yang et al, 1996). As shown in Fig.…”
Section: Rsbrmentioning
confidence: 99%
“…From these results, we conclude that: (i) RsbR is a positive regulator which probably belongs to the upstream, environmental-sensing module; (ii) RsbR augments response to salt and heat stress but is not absolutely required for sensing or transmitting these signals; and (iii) RsbR is unique among the known rsb gene products in that it is differentially involved in transmitting some but not all environmental stress signals. Significantly, genetic and biochemical analysis has established that the phosphorylation state of the RsbS, RsbV, and SpoIIAA antagonist proteins is important for their function, and that a conserved serine residue is the probable site of the phosphorylation event (Alper et al, 1994;Diederich et al, 1994;Dufour and Haldenwang, 1994;Najafi et al, 1995;Duncan et al, 1996;Kang et al, 1996;Yang et al, 1996). As shown in Fig.…”
Section: Rsbrmentioning
confidence: 99%
“…It was shown that the negative role of SpoIIAB was direct in that it bound F , thus acting as an anti-sigma factor; SpoIIAA antagonized the action of SpoIIAB and so is an anti-anti-sigma factor (51,199). SpoIIAB bore significant similarity to protein kinases, and it was found to phosphorylate SpoIIAA on a serine residue at position 58 (199,207). Mutation of this serine residue to an alanine (mimicking dephosphorylation) resulted in constitutive F activity, and mutation to an aspartic acid (mimicking phosphorylation) blocked F activity in vivo (44), indicating that the phosphorylation state of SpoIIAA is critical for its ability to function as an anti-anti-sigma factor.…”
Section: Posttranslational Regulation Of Fmentioning
confidence: 99%
“…Another area of ongoing research is the nature of the complexes that SpoIIAB forms with its binding partners. The basic model is that SpoIIAB inhibits F activity directly by binding to it and also indirectly by acting as a serine kinase that inactivates SpoIIAA by phosphorylating it (199,207). The phosphatase activity of SpoIIE functions to reverse this reaction (49), enabling SpoIIAA to attack the SpoIIAB-F complex and allowing F to become active.…”
Section: Mechanisms Of Compartmentalizationmentioning
confidence: 99%
“…In conclusion, it is interesting to note that bacteria contain another protein of the same lineage, the so-called anti-sigma factor SpoIIAB (29). Its sequence is very similar to the bacterial histidine kinases but, like PDK, contains a properly spaced glutamic acid in the N box.…”
Section: Active-site Titration With [␣-32 P]atp-ifmentioning
confidence: 99%